Evaluating Cone and Pyramid Frustums with Constant and Varying Wall Angles in Single-Point Incremental Sheet Forming - Bhasker R.S.; Kumar Y.; Kumar S.; Singh R. (My University, 2025)
Incremental sheet forming is a dieless forming process. Innovative analysis of deformations in the SPIF process, utilizing four distinct sets of deformed structures. Each set consists of four deformed shapes that are categorized as constant and variable tool path, as well as process characteristics including deformed shape, spindle speed, step size, and feed rate. The objective of this article is to investigate the variation of forming force, surface roughness, hardness value, strain rate, forming limit curve (FLC), and strain against forming depth and is to optimize its process parameters. Pyramid frustums have a lower surface roughness than conical frustums. Deformation depth affects hardness at different points along the frustum. The hardness value of the pyramid frustum is often higher than that of the conical frustum. As no single parameter is demonstrated to be significant in determining strain rate, the deformed shape is more relevant than the other process parameters. This effect is observed in the cone and pyramid frustums, where the cone frustum exhibits a higher strain rate than the pyramid frustum at a constant and variable wall angle. The result parameters increase; variation in decrease; variation in increase, and decline for different deformed shapes CWACF-1, 2, 3, 4, CWAPF-1, 2, 3, 4, VWACF-1, 2, 3, 4 and VWAPF-1, 2, 3, 4, respectively, under different other process parameters. The strain rate must not exceed the FLC to prevent sheet fracture, as FLC and strain vary with deformation depth for all deformed shapes. The deformed frustum, as well as the step size and other less influential criteria, have the greatest percentage contribution and impact on the findings of the research. © 2025 SAE International.